Priscilla and the pink planet - Hobbie, Nathaniel; Hobbie, Jocelyn (New York : Little, Brown, 2004)
Tired of seeing the color pink, Priscilla encounters the Pink Planet's Great Queen of Pink and tries to convince her of the need for a variety of colors.
3.2
K-3
K-3
School Library Journal
Book Links (A.L.A.)
Publisher's Weekly
Keywords: Colors -- Juvenile fiction; Planets -- Juvenile fiction; Color -- Fiction; Planets -- Fiction; Stories in rhyme; Color -- Fiction; Planets -- Fiction; Stories in rhyme